A JOB TRAINING REPORT AS A SECRETARY AND PUBLIC RELATION ASSISTANT AT PT.TELEKOMUNIKASI INDONESIA, TBK SURABAYA FROM JANUARY 16TH,2017 TO FEBRUARY 24TH, 2017 - SHOFI RIZKI ANASANTI, 151411813091 (2017)
In this globalization era, communication is necessary for people around the world. It can help them to communicate with other people. There are telecommunication companies in Indonesia. One of the biggest telecommunication companies is PT.Telekomunikasi Indonesia, Tbk often called as PT.TELKOM. PT. TELKOM is one of the world’s oldest and biggest telecommunication companies. There are several divisions in PT. TELKOM . One of them is Secretary and Public Relation Division. The writer did her internship at PT. TELKOM for six weeks started from 16th January until 24th February 2017. The writer was assigned in Secretary and Public Relation Division as a secretary. In the writer’s opinion, having an internship at PT. TELKOM was really worthy. The writer could apply the knowledge that she has got from activity of learning in the campus. The writer also improves the soft skills that she has been taught such as discipline, socializing, honesty, and communication. As long as the writer does her internship, she does some duties. They are to organize and maintain files, maintaining diaries and arranging appointments, typing, preparing and collating reports, making letters such as invitation letters, incoming and outgoing the phone, sending letters and invitation letters by fax and email, Implementing new procedures and administrative systems, Managing reception, meeting and greeting clients, filing, and editoring meeting. The writer not only does some duties but also learn about how to work efficiently in groups and individually, how to adapt to the environment in the workplace, and how to be responsible with all the duties that given. The writer also learns more about discipline, because the writer has to come on time during her working time. Communicating with people from various backgrounds is also learned by the writer during the job training. Doing the internship in the biggest telecommunication company in Indonesia, PT.TELKOM, the writer not only has obtained a valuable experience, but also feels proud and grateful to be a part of it. In conclusion, doing internship at PT. TELKOM especially in Secretary and Public Relation Division has given some benefits for the writer and make the writer ready to come to the real workplace in the future. As an internship student in PT. TELKOM, the writer recommends PT. TELKOM as a place to do internship for anyone who wants to learn more about telecommunication business. The writer also suggests that PT. TELKOM keep accepting the internship students who want to do the internship there. In addition, the writer had suggestion for PT. TELKOM. There are several suggestions, In order to improve the performance from the staffs in PT. TELKOM, especially staffs in Secretary and Public Relation Division. First, they have to practice English skill both oral and written because they do a cooperation with international company, such as Huawei, Singapore, and and Malaysia. If they apply the English skills, it will probably make their work become easier. The writer also suggests for PT. TELKOM, especially in Secretary and Public Relation Division to add more staffs in this division because the writer thinks that the number of the staffs in there is not enough to handle all of the cooperation. If they add more staffs, it will make their work become more efficient and effective. The writer also hopes that PT. TELKOM will always become a leading telecommunication company as it is now, so there will be more rewards that can be achieved in the future.